Effect of Nosocomial Bloodstream Infections on Mortality, Length of Stay, and Hospital Costs in Older Adults. Issue 2 (17th January 2014) - Kaye, Keith S.; Marchaim, Dror; Chen, Ting‐Yi; Baures, Timothy; Anderson, Deverick J.; Choi, Yong; Sloane, Richard; Schmader, Kenneth E
<x xml:space="preserve">Abstract</x> Objectives To quantify the effect of nosocomial bloodstream infection (BSI) on older adults, including mortality, length of stay (LOS), and costs attributed to BSI. Design Retrospective cohort study. Setting Eight acute care hospitals (7 community hospitals and 1 tertiary university‐affiliated facility) belonging to the Duke Infection Control Outreach Network (DICON) from the states of North Carolina and Virginia. Participants Elderly patients over 65 years of age. Measurements A multistate, multicenter, matched, retrospective cohort study was conducted from January 1994 through June 2002 in eight hospitals from the Southern‐Central United States. Patients aged >65 years with nosocomial BSI were enrolled. Controls without bloodstream infection were matched to cases. Outcomes during the 90‐day period following hospital discharge were evaluated to determine the association between BSI and mortality, hospital costs, and LOS. Results Eight‐hundred thirty cases and 830 matched controls were identified, all with a mean age of 74.4 years. Among cases, 81% of BSIs were central line‐associated and Staphylococcus aureus was the most common pathogen accounting for 34.6% of infections (2/3 were methicillin resistant). The mortality rate of cases was 49.4%, compared to 33.2% for controls (OR = 2.1, P < .001), LOS was 29.2 days for cases and 20.2 days for controls (P < .001), and hospital charges were $102, 276 for cases compared to $69, 690 for controls (P < .001). The mean LOS and mean costs attributable to BSI were 10 days and $43, 208, respectively. Conclusion Nosocomial BSI in older adults was significantly associated with increases in 90‐day mortality, increased LOS, and increased costs of care. Preventive interventions to eliminate nosocomial BSIs in older adults would likely be cost effective.